Identification of hsa-miR-619-5p and hsa-miR-4454 in plasma-derived exosomes as a potential biomarker for lung adenocarcinoma - Feng, Linxiang; Feng, Zian; Hu, Jie; Gao, Jiahui; Li, Ang; He, Xiaodong; Liu, Liu; Shen, Zuojun (Frontiers in Genetics, 2023)
Lung cancer has long been at the forefront of all cancers in terms of incidence and mortality. Lung adenocarcinoma is the most common type of lung cancer, accounting for 40% of all lung cancer types. Exosomes can act as biomarkers of tumors and thus play an important role. In this article, high-throughput sequencing of miRNAs in plasma exosomes from lung adenocarcinoma patients and healthy individuals was performed to obtain 87 upregulated miRNAs, which were then combined with data from the GSE137140 database uploaded by others for screening. The database included 1566 preoperative lung cancer patients, 180 postoperative patients, and 1774 non-cancerous controls. We overlapped the miRNAs upregulated in the serum of lung cancer patients in the database relative to those of non-cancer controls and post-operative patients with the upregulated miRNAs obtained from our next-generation sequencing to obtain nine miRNAs. Two novel miRNAs, hsa-miR-4454 and hsa-miR-619-5p, not reported in lung cancer, were selected and then validated by qRT-PCR, and further analysis of miRNAs was performed using bioinformatics. The results revealed a significant upregulation of miRNAs in plasma exosomes from lung adenocarcinoma patients. Our work demonstrated that hsa-miR-4454 and hsa-miR-619-5p can be used as biomarkers for the early diagnosis of lung adenocarcinoma.